Evaluasi in vitro dan in silico aktivitas toksikologi dan anti proliferasi senyawa fitokimia beberapa ekstrak pelarut dari Zaleya Pentandra L - Elsamani, Mohamed O. (Journal of Pharmaceutical and Sciences, 2024)
Therapeutic plants and herbals are vital superior nutrient resources mainly used in diet and recognised for treating various diseases. The study's main objective is to investigate phytochemicals compounds, antioxidant and antibacterial activities on five Zaleya pentandra extract (ZPE), ethanol, hexane, acetone, ethyl acetate, and methanol for the first time.  Methods: The study was conducted using the HPLC-MS, and measurements were made in three replicates.  Results: The most significant extracts, revealing 13compounds, which appear higher content (417.5±0.44 μg/g and (407.5±0.04 μg/g), value of ZPE in total β-Sitosterol and dioctyl phthalate, respectively, also the total polyphenol content (TPC) was significantly (p≤0.05) higher mainly in acetone (323.06±1.74mg GAE/g), ethyl acetate (220 ± 1.00) mg GAE/g), and hexane herbal extracts (75.2±1.70) mg QE/g) with a significant difference (P≤0.05) in total flavonoid content. Discussion: All investigated bacterial strains had an exceptionally high effect against B. subtilis. A computational analysis qualified a significant drug-likeness feature, including toxicological and pharmacokinetic assessments. ZP acetone extract is an appropriate selection for creating contemporary antibacterial compounds. Conclusions: The current study offers new information on applying ZPE in novel and potentially effective therapeutic agents, its application in the food industry, and the treatment of different diseases.